A double-edged sword? Identifying the influence of peers, mass and social media on engagement in mobile phone use while driving. (May 2022) - Stefanidis, K.B.; Truelove, V.; Freeman, J.; Mills, L.; Nicolls, M.; Sutherland, K.; Davey, J.
Highlights: Almost two thirds (63%) of the sample reported using their mobile phone while driving at some time point. Exposure to social media content encouraging phone use while driving predicted increasing engagement in the behaviour. Peer engagement in phone use while driving predicted increasing engagement in the behaviour. Exposure to mass media content encouraging phone use while driving did not influence the behaviour. Abstract: While the ever-expanding proliferation of social media is well documented, the relationship such exposure has upon road rule compliance remains completely unknown. Further, it is not clear as to whether social media independently affects such behaviour, when accounting for the influence of mass media and peers. As a result, this study examined the relative influence of exposure to content that encourages phone use while driving via these three mediums in order to identify the most salient stimuli. A total of 509 participants (aged 17–88 years, M =  33, SD =  17) from the state of Queensland, Australia, were included in this study. Participants completed an online survey, which examined self-reported levels of exposure to material encouraging hand-held mobile phone use while driving from three sources: mass media (e.g., television, movies and gaming), social media, and peer behaviour (descriptive norms). Results indicated that participants on average engaged in illegal mobile phone use while driving 16% of the time they drive. Exposure to material encouraging phone use while driving was significantly higher from mass media ( M  = 32% of the time) and via peers ( M  = 30%) compared to social media ( M =  27%). However, only social media and peer behaviour (the frequency with which participants believed that their peers engage in the behaviour) significantly predicted engagement in self-reported illegal mobile phone use, such that increasing levels of exposure were associated with more frequent use while driving. These findings: (a) support an emerging body of evidence indicating that both peer behaviours and social media messages are highly salient and influential and (b) are the first to suggest that such exposure might directly affect road safety. Nonetheless, further research is warranted to elucidate the nature and direction of the relationship between social media and driving behaviour, and the mechanisms through which such messages influence behaviour. Such lines of enquiry would have important implications for road safety (e.g., by informing the development of countermeasures/interventions delivered via social media).